The Role of Melatonin, IL-8 and IL-10 in Intrahepatic Cholestasis of Pregnancy - Çelik, Samettin; Guve, Huri; Çalışkan, Canan; Çelik, Sebahattin (Zeitschrift für Geburtshilfe und Neonatologie, 2020)
Introduction Intrahepatic cholestasis of pregnancy is a pregnancy-specific liver disease that usually emerges during the third trimester of pregnancy. It is characterized by itching and elevated serum total bile acid levels, and it may lead to severe fetal complications. This study aimed to investigate the role of interleukin-8, a pro-inflammatory cytokine; interleukin-10, an anti-inflammatory cytokine; and melatonin in intrahepatic cholestasis of pregnancy.Materials and Methods This prospective, case-controlled study was conducted with 51 women with intrahepatic cholestasis of pregnancy (40 mild and 11 severe cases) and 43 healthy pregnant women. Serum interleukin-8, interleukin-10, and melatonin levels were evaluated.Results Melatonin and interleukin -10 were significantly lower in subjects with intrahepatic cholestasis of pregnancy (p=0.001; p=0.001, respectively p<0.05). Interleukin-8 levels were found to be significantly higher in the cholestasis group than control group (p=0.001, p<0.05).Conclusions Because interleukin-8, interleukin-10, and melatonin were found to be significantly correlated with intrahepatic cholestasis of pregnancy, we believe this finding could shed light on the etiology of the disease.
Keywords: Intrahepatic cholestasis of pregnancy; melatonin; interleukin-8; interleukin -10